Prevalence of E. coli as a causative agent of urinary tract infections and its drug susceptibility patterns among pregnant mothers seeking medicare at Kisii teaching and referral hospital, Kenya - Simba, Sosmus M.; Omwenga, Eric O.; Musyoki, Stanslaus K. (International Journal Of Community Medicine And Public Health, 2022)
Background: E-coli, a gram-negative entero-bacteria has been associated with urinary tract infections (UTIs) and antimicrobial resistances in human and animals. This study aimed at establishing the prevalence of E. coli among other bacteria causing UTIs in pregnant women seeking Medicare at Kisii teaching and referral hospital (KTRH), Kenya and to establish the drug susceptibility patterns of the isolated E. coli. Setting-The project was done at Kisii teaching and referral hospital, Kenya. Methods: This hospital based experimental and cross-sectional study conducted in 3 months between March and June 2020 involved 119 pregnant women whose urine samples were cultured on Cysteine Leucine Electrolyte deficiency media (CLED) at 370C overnight and sub-cultured on Mueller Hinton media. Bacterial identification was done by Gram stain and biochemical characterization using indole, methyl-red, Voges-Proskaur and citrate tests while susceptibility tests were conducted by Kirby Bauer disc diffusion technique. Results: Out of the 119 urine samples, E. coli 28 (23.5%) was the second most prevalent after S. aureus 40 (33.6%). Others included S. epidermidis 27 (22.7%), and Proteus spp. 9 (7.6%). All E. coli isolates, 28 (100%) demonstrated resistance to sulfamethoxazole followed by amoxyclave 24 (85.75%), and ceftriaxone 20 (71.42%). They were least resistant to gentamycin 4 (14. 28%) and ofloxacin 6 (21.42%). Conclusions: E. coli which largely exists as a commensal can cause UTIs and could be possessing antimicrobial resistant genes responsible for treatment failure. This demands for new effective therapeutic alternatives and more research on bacterial drug resistant.